Foreword - POP-CURȘEU, Ioan (Studia Universitatis Babeș-Bolyai Dramatica, 2020)
This special issue of Studia UBB Dramatica is devoted to a research topic developed in a project supported by the Ministry of Education and Research, in a grant Uefiscdi PN-III-P1-1.1-TE-2016-0067, contract number 135/2018, with the title Iconography of Witchcraft, an Anthropological Approach: Cinema, Theatre, Visual Arts (Iwacta). In the Romanian cultural context, the implementation of the project seemed very important from a scientific and institutional point of view, by its possibilities of making some significant contributions to the field of visual anthropology.